1992
DOI: 10.1007/bf00039921
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis, plant regeneration and somaclonal variation in barley

Abstract: In vitro culture of immature embryo and young leaf tissues was carried out with five cultivars of barley, Hordeum vulgare. Two cultivars (Albacete and Porthos) responded poorly from both types of explants, while the three others (Dissa, Golden Promise and Ingrid) produced a high frequency of embryogenic callus from these explants (25-60%). For 'Dissa' and 'Ingrid', young leaf explants were slightly better than immature embryo explants for embryogenic callus induction, while immature embryo cultures of 'Golden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Yellowish and crumbly calluses originated on the medium with 2,4-D; creamy white to transparent, compact and soft calluses originated on the medium with dicamba. The same type of callus was also observed by Ruíz et al (1992), Bregitzer et al (1995) and Castlillo et al (1998).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Yellowish and crumbly calluses originated on the medium with 2,4-D; creamy white to transparent, compact and soft calluses originated on the medium with dicamba. The same type of callus was also observed by Ruíz et al (1992), Bregitzer et al (1995) and Castlillo et al (1998).…”
Section: Discussionsupporting
confidence: 80%
“…However, in some cases phenotypic and cytological variants have been found among regenerated barley plants (Karp et al 1987). In barley differences in the production of embryogenic calluses and regenerated plants have been observed when cultures were initiated from leaf base/apical meristems, mature embryos (Ganeshan et al 2003), immature inflorescences (Thomas and Scott 1985) immature zygotic embryos (Lührs and Lörz 1987, Ruíz et al 1992, Chang et al 2003) and immature scutella (Tingay et al 1997). But immature zygotic embryos are currently the most reliable and efficient target tissue for in vitro regeneration of cereals, this has already been well documented in some reports by Dahleen and Bregitzer (2002) and Chang et al (2003).…”
mentioning
confidence: 99%
“…In this study, interaction of genotype × explant played an important role in the somatic embryogenesis of rye. A similar interaction has been found in barley (Ruiz et al 1992). …”
Section: Differences Of Somatic Embryogenesis Between Plant Organs Ofsupporting
confidence: 79%
“…[50], Elaeis guineensis [51] Actinidia deliciosa [52], and Phoenix dactylifera [53]. In Arabidopsis, 66.7% of the analysed regenerated plants showed at least one polymorphism [4], while for barley, the literature data is controversial, since Ruiz et al [6] found that somaclonal variation did not appear to be a very frequent event, while Bednarek et al [54] reported that all the regenerated plants showed at least one polymorphism with respect to the control plant. By contrast, our research revealed a high rate of changes among the plantlets, since 97.4% of them scored at least one polymorphic band relative to the control plant, even though the regenerated H. italicum plantlets showed a high identity, sharing on average more than 99.3% of the AFLP fragments.…”
Section: Discussionmentioning
confidence: 99%
“…storage protein levels in cereals and legumes), analyzing genotypic variations requires more appropriate tools, particularly considering that such variations do not necessarily lead to phenotype variations of agricultural value. The use of molecular markers can accomplish this task, and indeed they have been widely employed for the identification of somaclonal variants [5], with greater precision and less effort than karyological and phenotypic analyses [6,7]. Several marker classes are employed, but each has some disadvantages.…”
Section: Introductionmentioning
confidence: 99%